PENERAPAN MEDIA RUMAH BILANGAN UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS II MURID TUNAGRAHITA RINGAN DI SDN WONOREJO V SURABAYA - NOVITASARI, DIAN; MAHMUDAH, SITI (Jurnal Pendidikan Khusus, 2018)
Based on the observation, the average score of the place value numbers of the second graders with mild intellectual disability at SDN Wonorejo V Surabaya were quite low. One of the causes was due to lack of planning in preparing learning materials. This study aims to improve the learning results in mathematics especially the place value numbers among the 2nd grade students of SDN Wonorejo V with mild intellectual disability. The study applied Classroom Action Research (CAR) to the 2nd grade students of SDN Wonorejo V with mild intellectual disability as the subjects. Data were collected through observation, test, and documentation and data were analized using percentage. The results showed that the pre-cycle score was 37.5 with being 0% of learning completeness, being 50% of learning completeness in the 1st cycle, and being 100% of learning completeness in the 2nd cycle with 65% predefined learning completeness standard. The results showed that 2nd grader students with mild intellectual disability experienced a change in understanding the place value number and proved that applying the house number as learning media was able to improve the student learning result on 2nd grader students with mild intellectual disability at SDN Wonorejo V Surabaya. Keywords : Learning Media, Mathematics Learning Result